Transition Management Towards Merdeka Curriculum at Early Childhood Education Not School Mover (Case Study 5 Kindergartens Jepara) - Nadiatus Shofaa Sabila; Ali Formen; Joko Sutarto (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
This research examines the transition of merdeka curriculum at early childhood education in 5 kindergarten institutions in Jepara city. The research focus of this study includes transition management of merdeka curriculum, implementation of transition management of merdeka curriculum, and supporting and inhibiting factors. The findings of this research are that in implementing transition management to merdeka curriculum, the curriculum is designed contextually so that it makes it easier for educators to implement it. In addition, the planning process must involve related parties so that it can support the implementation of an effective and efficient transition of merdeka curriculum. Supporting factors include stakeholders and organizations such as IGTKI, KKG, and groups that facilitate training or discussions related to the merdeka curriculum, cooperation between educators, and collaboration between parents. The conclusion of this research is that transition management of merdeka curriculum at early childhood education makes a significant contribution to institutions that are still confused about deciding on the transition to merdeka curriculum.